PEMANFAATAN PEKARANGAN SEKOLAH DASAR SEBAGAI MEDIA PEMBELAJARAN PERTANIAN HORTIKULTURA PRODUKTIF - Khasanah, Nur; Muharani, Laily; Priestiani, Priestiani; Varentinus, Steven; Madiza, M Rezi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The schoolyard is one of the places that can be used as a learning media for elementary school students. Students can learn outside the classroom to support creativity and increase knowledge related to the environment. The utilization of the yard can be realized through vegetable gardening activities as a form of students and teachers in utilizing the potential of natural resources and the environment. The utilization of the schoolyard through training on the introduction and planting of horticultural plants can be used as an educational tool in shaping student character, so that students will know and care about the environment. The character of students can be formed and influenced by the learning they acquire at school because students spend most of their time at school. The utilization of the elementary school yard as a medium for horticultural agricultural learning is carried out by introducing conventional agriculture by utilizing natural resources and the schoolyard to be used as a learning facility. So that students have additional knowledge about horticultural plant cultivation, students can read opportunities in utilizing the surrounding environment or home yards to be used as a place for plant cultivation, and Schools can utilize the yard as a learning medium. The methods used in this PkM are lecture, participatory, and demonstration methods. The results of the PkM showed an increase in understanding and knowledge of the field of agriculture from 19.59% to 80.41%. So it can be concluded that the PkM activities provide benefits for students and schools.